Studi Potensi Airtanah Dan Kebutuhan Domestik Desa Batujajar Timur Kabupaten Bandung Barat - Aszka Saffanah Syahrazadh; Yusuf Fathurrahman; Nabila Ayu Azzahra; Dian Arsyka Adila; Rizka Novi Ramadhani; Azzahra Gita Putri Anjani; Dini Fadhilah Utami; Endra Yuliawan; Sonna Diwijaya; Hilmy Ahmad; Pramuditya Vanesya Putri F. A; Tjahyo Nugroho Adji (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2026)
Groundwater potential studies are crucial for sustainable water management because groundwater quality tends to be superior and more widely utilized by the community compared to surface water. This high dependency potentially triggers an imbalance between domestic water availability and demand. This study aims to map flow patterns, calculate availability potential, evaluate domestic demand, and test the groundwater quality index in Batujajar Timur, West Bandung Regency. The methods used in this research include field measurements of water table levels, geoelectrical surveys using the VES method, pumping tests using the Shallow Dug Well Recovery Test (Slug Test) method, and water quality index testing using a modified GWQI method. Batujajar Timur has a groundwater flow pattern that directs from the hilly topography toward the lowlands, specifically from east to west. This aligns with the lithology forming the area, where tuffaceous breccia rocks form irregular ridges in the northern and eastern parts. The static groundwater availability potential at the study site was determined to be 5,226,543,302.41 liters/year, with a hydraulic conductivity value of 2.24 m/day, classified as fine sand. The dynamic groundwater availability potential was found to be 293,192,067.24 liters/year. The domestic demand of the population at the research location is 694,317,568.8 liters/year. The physical quality of groundwater in residents' wells shows values exceeding the quality standards, which is further evidenced by GWQI calculation results at two well points indicating a very poor water quality class.